TAXONOMY OF TRAINING ACTIVITIES IN THE STUDY OF PSYCHOLOGY (Global Economic Review: Journal of Economics, Policy, and Business Development, 2025)
The article describes the educational activities, technical methods, technologies in teaching psychology, their content, and the opinions of scientists.